Analysis of Energy Consumption by Electric Agricultural Tractor Model Under Operating Conditions (Agricultural Engineering, 2021)
The aim of the paper is analysis of consumption of electric energy which is necessary to drive a farm tractor with an electric motor as a drive unit under the conditions of a drive with varied loading of the power transmission system. The object of the research was a tractor model where a combustion engine was replaced with a dc electric motor. During the tests, a decrease of voltage and current strength collected from supplying batteries as a function of tractor drive time and in relation to the mass of a tractor with a trailer, temperature of the surrounding and resistance to motion were reported, which enabled determination of the collected power and energy. For the used set of batteries, also the maximum range of the tractor drive on the paved road was determined.